Geographic Disparities in Case Fatality and Discharge Disposition Among Patients With Primary Intracerebral Hemorrhage - Bako, Abdulaziz T.; Potter, Thomas; Pan, Alan; Tannous, Jonika; Rahman, Omar; Langefeld, Carl; Woo, Daniel; Britz, Gavin; Vahidy, Farhaan S. (Journal of the American Heart Association, 2023)
Background We evaluate nationwide trends and urban-rural disparities in case fatality (in-hospital mortality) and discharge dispositions among patients with primary intracerebral hemorrhage (ICH). Methods and Results In this repeated cross-sectional study, we identified adult patients (≥18 years of age) with primary ICH from the National Inpatient Sample (2004-2018). Using a series of survey design Poisson regression models, with hospital location-time interaction, we report the adjusted risk ratio (aRR), 95% CI, and average marginal effect (AME) for factors associated with ICH case fatality and discharge dispositions. We performed a stratified analysis of each model among patients with extreme loss of function and minor to major loss of function. We identified 908 557 primary ICH hospitalizations (overall mean age [SD], 69.0 [15.0] years; 445 301 [49.0%] women; 49 884 [5.5%] rural ICH hospitalizations). The crude ICH case fatality rate was 25.3% (urban hospitals: 24.9%, rural hospitals:32.5%). Urban (versus rural) hospital patients had a lower likelihood of ICH case fatality (aRR, 0.86 [95% CI, 0.83-0.89]). ICH case fatality is declining over time; however, it is declining faster in urban hospitals (AME, -0.049 [95% CI, -0.051 to -0.047]) compared with rural hospitals (AME, -0.034 [95% CI, -0.040 to -0.027]). Conversely, home discharge is increasing significantly among urban hospitals (AME, 0.011 [95% CI, 0.008-0.014]) but not significantly changing in rural hospitals (AME, -0.001 [95% CI, -0.010 to 0.007]). Among patients with extreme loss of function, hospital location was not significantly associated with ICH case fatality or home discharge. Conclusions Improving access to neurocritical care resources, particularly in resource-limited communities, may reduce the ICH outcomes disparity gap.